2021
DOI: 10.3389/fcell.2021.656741
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index (PNI) in Patients With Breast Cancer Treated With Neoadjuvant Chemotherapy as a Useful Prognostic Indicator

Abstract: ObjectivePrognostic nutritional index (PNI), calculated as serum albumin (ALB) (g/L) + 5 × total lymphocyte count (109/L), is initially used to evaluate nutritional status in patients undergoing surgery and may evaluate the therapeutic effects and predict the survival of various solid tumors. The present study aimed to evaluate the potential prognostic significance of PNI in breast cancer patients receiving neoadjuvant chemotherapy (NACT).MethodsA total of 785 breast cancer patients treated with neoadjuvant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 51 publications
(52 reference statements)
6
75
1
1
Order By: Relevance
“… 24 , 46 The PNI was summed using serum albumin levels and the peripheral lymphocyte counts, which have been proven to reflect the nutritional status of patients and are associated with their survival in many studies. 28 , 47 Elevation of the ALP level, another serum biological factor reflecting the nutritional status of humans, might represent a heavy tumor burden. 26 The AAPR is calculated by dividing the serum albumin level by the serum ALP level, and its prognostic value in several cancers has been commonly recognized, 48–50 similar to our previous study on patients with nonmetastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 , 46 The PNI was summed using serum albumin levels and the peripheral lymphocyte counts, which have been proven to reflect the nutritional status of patients and are associated with their survival in many studies. 28 , 47 Elevation of the ALP level, another serum biological factor reflecting the nutritional status of humans, might represent a heavy tumor burden. 26 The AAPR is calculated by dividing the serum albumin level by the serum ALP level, and its prognostic value in several cancers has been commonly recognized, 48–50 similar to our previous study on patients with nonmetastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between obesity and an elevated risk of breast tumors might promote cancer-related inflammation, and PNI could be a convenient and useful biomarker for personalized therapeutic decisions for breast cancer. 27 , 28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, tumor dyscrasia can also often lead to hypocholesterolemia in patients. It is well established that nutritional status as assessed by PNI and CONUT is significantly associated with the prognosis of patients with several malignancies, including breast (11), colorectal (12), lymphoma (13), esophageal (14), pancreatic (15), and cervical cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that low AGR or high SIRI is associated with poorer survival outcomes [6][7][8]. Nutritional and in ammatory indicators are related to the prognosis of patients with cancer [2,9,10]. Nevertheless, these studies focused on a single marker, patients at a certain stage, or a particular cytological classi cation.…”
Section: Introductionmentioning
confidence: 99%